Code-switching and code-mixing in indonesian learning at SMA YP Unila - Fuad, Muhammad; Suyanto, Edi; Mustofa, Ali; Amala, Istiqomah Ahsanu; Muhammad, Ulul Azmi (Universitas Lampung, 2023)
The purpose of this research is to seek information about the factors causing code switching and code mixing in the post-pandemic learning process of the Indonesian language in class XII Social Sciences at SMA YP Unila. This study uses a descriptive approach. The data collected are in the form of words, pictures, and not numbers. This research leads to an in-depth description of the meaning, clarification, and placement of data in their respective contexts and describes them in the form of words from numbers. The total code-switching in learning interactions is one-word data, two phrases, and five sentences; this shows that students' and teachers' interest in code-switching in both classes is shallow. As in code-switching, the form of code mixing in its interaction is divided into internal code-mixing and external code-mixing. In internal code-mixing, the language used is the insertion of Javanese in Indonesian sentences. Meanwhile, in external code-mixing, the language used is the insertion of English and Arabic in the interaction of Indonesian language learning. The implication aims to make it easier for teachers and students to understand word insertion during learning interactions and quickly understand what other people say when communicating. Keywords: Code-Switching, Code-Mixing, Indonesian Learning